2020
DOI: 10.1007/s00068-020-01401-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the assessment of non-technical skills by using video-recorded trauma resuscitations

Abstract: Purpose Non-technical skills have gained attention, since enhancement of these skills is presumed to improve the process of trauma resuscitation. However, the reliability of assessing non-technical skills is underexposed, especially when using video analysis. Therefore, our primary aim was to assess the reliability of the Trauma Non-Technical Skills (T-NOTECHS) tool by video analysis. Secondarily, we investigated to what extent reliability increased when the T-NOTECHS was assessed by three assessors [average i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The ability to replay cases further highlights the advantages of the Trauma Team Video Review Program, as it limited the possibility of recall bias and allowed for details related to case specifics to be reviewed and accurately collected [ 14 ]. In addition, we used two reviewers, corroborating with the study performed by Maarseveen et al [ 24 ] which suggested that video analysis of trauma team performance by multiple raters using T-NOTECHS leads to a higher ICC compared to resuscitations observed by live raters, suggesting greater reliability. As such, from a methodological perspective, having two reviewers collect data using video review technology allowed for more robust data collection in our study.…”
Section: Discussionsupporting
confidence: 81%
“…The ability to replay cases further highlights the advantages of the Trauma Team Video Review Program, as it limited the possibility of recall bias and allowed for details related to case specifics to be reviewed and accurately collected [ 14 ]. In addition, we used two reviewers, corroborating with the study performed by Maarseveen et al [ 24 ] which suggested that video analysis of trauma team performance by multiple raters using T-NOTECHS leads to a higher ICC compared to resuscitations observed by live raters, suggesting greater reliability. As such, from a methodological perspective, having two reviewers collect data using video review technology allowed for more robust data collection in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Trauma Nontechnical Skills Scale has widely been used in a trauma setting for teaching purposes and to assess the learning outcomes and teamwork skills of multidisciplinary trauma teams 45 . Trauma Nontechnical Skills Scale is a simple and validated instrument in assessing the nontechnical skills of trauma teams, which may be rapidly adopted by raters of varying expertise (medical students to experienced clinicians) after minimal training 46 . However, studies such as conducted by Wieck et al 43 suggest that T-NOTECHS may still benefit from further refinement, such as increasing the accuracy of the scoring system through mixing expert and self-reported assessments for different domains.…”
Section: Discussionmentioning
confidence: 99%
“…45 Trauma Nontechnical Skills Scale is a simple and validated instrument in assessing the nontechnical skills of trauma teams, which may be rapidly adopted by raters of varying expertise (medical students to experienced clinicians) after minimal training. 46 However, studies such as conducted by Wieck et al 43 suggest that T-NOTECHS may still benefit from further refinement, such as increasing the accuracy of the scoring system through mixing expert and self-reported assessments for different domains. On the other hand, TEAM is an instrument that was designed to assess nontechnical skills more broadly during resuscitation events (extending beyond trauma teams, such as cardiac resuscitation teams), which may be applied for quality improvement research or teaching purposes.…”
Section: Practical Application Of Team Assessment Toolsmentioning
confidence: 99%
“…In simplest form, the impact of team variance on teamwork could be assessed during simulation sessions to compare teams with no or little variance to high variance. There are reliable and validated tools available to assess the teamwork, such as the T-NOTECHS tool [22][23][24]. Third, interventions to effectively reduce team variation could be developed, tested and implemented into practice.…”
Section: Further Researchmentioning
confidence: 99%